A Composite Neoclassical Toroidal Viscosity Model Incorporating Torques from both Axisymmetric and Nonaxisymmetric Tokamak Magnetic Fields. (19th May 2019) - Stacey, Weston M.
Abstract: This paper combines the older neoclassical gyroviscous model for toroidal viscosity in the plasma core, which is based on an axisymmetric magnetic field and obtains reasonable agreement with experiment for toroidal rotation in the plasma core but not in edge plasma, with recent models for neoclassical toroidal viscosity (NTV) based on nonaxisymmetric "perturbation" magnetic field components present primarily in the edge plasma to obtain a composite toroidal viscosity model for toroidal velocity calculations in the tokamak core and edge plasma. This combination is facilitated by the fact that the same form of "drag frequency" representation of the viscous torque used in many of the new (NTV) torque models arising from toroidally nonaxisymmetric perturbation magnetic fields that are present mostly in the plasma edge can also be used to represent the old neoclassical toroidal viscous torques arising from toroidally axisymmetric magnetic fields.